Evaluation of the gastric microbiota based on body mass index using 16S rRNA gene sequencing - Lee, Sang Hoon; Kim, Eun Bae; Park, Sung Chul; Nam, Seung-Joo; Cho, Hyunseok; Jeon, Han Jo; Lee, Sang Pyo (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionObesity is a multifactorial condition influenced by various factors, including the gut microbiota. However, the relationship between the gastric microbiota and obesity remains poorly understood. This study aimed to investigate the composition of gastric microbiota, excluding Helicobacter pylori, in relation to body mass index (BMI) and metabolic indicators.MethodsThirty participants undergoing health checkups were classified into three groups—normal weight (BMI 18.5–22.9), overweight (BMI 23.0–24.9), and obese (BMI ≥25.0)—with ten individuals per group. Those with H. pylori infection, atrophic gastritis, or intestinal metaplasia were excluded. Gastric microbiota from four antral biopsies per subject were analyzed using 16S rRNA sequencing and functional profiling by metagenomic prediction.Results and discussionAlpha diversity (Gini–Simpson index) was significantly lower in the combined overweight/obese group than that in the normal group (P=0.049). Beta diversity analysis revealed clear group separation (Bray–Curtis, P=0.005; unweighted UniFrac, P=0.004). Significant species differences between the groups were observed; specifically, the abundances of Muribaculum gordoncarteri, Turicibacter bilis, and Duncaniella dubosii, were significantly reduced in the overweight/obese group. Functional predictions showed differential enrichment of pathways related to fatty acid, amino acid, vitamin, and carbohydrate metabolism across BMI categories. These findings suggest that alterations in the gastric microbiota may be linked to obesity and metabolic dysregulation.